2010
DOI: 10.3844/ajptsp.2010.119.124
|View full text |Cite
|
Sign up to set email alerts
|

The Intracerebroventricular Administration of W-7, A Calmodulin Inhibitor, Attenuate the Development of Morphine Tolerance in Rats

Abstract: Problem statement: The present study was performed to determine the effect of Intracerebroventricular (ICV) administration of W-7, a specific calmodulin inhibitor, on the analgesic effect and development of tolerance to antinociceptive effect of acute and chronic morphine administration respectively. Approach: This study was carried out on male wistar rats, weighing 200-250 g. For acute experimental protocol, Morphine was injected intraperitonealy in a single dose (5 mg kg −1 ). For chronic experimental protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…: 10 mg/kg for 8 days) caused tolerance to the antinociceptive effects of morphine during the formalin test. It has been reported that intraperitoneal injection of chronic administration of morphine induces morphine tolerance in tail flick and hot plate test (Javan et al, 2003;Sepehri et al, 2010). The present data also indicated that acute administration of morphine (i.p.…”
Section: Discussionsupporting
confidence: 81%
“…: 10 mg/kg for 8 days) caused tolerance to the antinociceptive effects of morphine during the formalin test. It has been reported that intraperitoneal injection of chronic administration of morphine induces morphine tolerance in tail flick and hot plate test (Javan et al, 2003;Sepehri et al, 2010). The present data also indicated that acute administration of morphine (i.p.…”
Section: Discussionsupporting
confidence: 81%